INSEGUROS Y LIBRES: VULNERABILIDAD Y RESILENCIA EN EL LÉXICO POLÍTICO-JURÍDICO DEL NEOLIBERALISMO - Marzocco, Valeria (Gênero & Direito, 2016)
Over the past few years, the political and legal debate of government’s new strategies about social complexity has been followed by the representation of individual and collective increasing vulnerability imposed by the process of transformation that has affected the concept of risk. The scenario returned by threat exposure coming from the representation of global political uncertainty actives human decision in a perspective that changes concept and historical form that risk definition process offered to modern society. In these terms, either vulnerability concept or resilience model functionalize a representation describing the exposition to uncertainty offered by the crisis of the calculable risk definition: they conceptually return to an appeal of explicative ability of categories and meanings attributed by theories of complexity borrowers of an epistemological approach of natural science defining the possible government policy in a scenario characterized by fast and unpredictable changes